The relationship between genotype and phenotype in Chinese children with glucose transporter type 1 deficiency syndrome - Zhang, Mei-Jiao; Zhang, Shi-Min; Zhang, Qing-Ping; Wen, Yong-Xin; Wang, Jia-Ping; Xiong, Hui; Jiang, Yu-Wu; Bao, Xin-Hua (Frontiers in Neurology, 2025)
BackgroundGlucose transporter type 1 deficiency syndrome (Glut1DS) is a treatable neurogenetic metabolic disorder caused by pathogenic variants in the SLC2A1 gene. The relationship between genotype and phenotype has not been extensively studied in large cohorts within China. This study aimed to analyze the clinical and genetic characteristics and the genotype-phenotype correlation in Chinese children with Glut1DS.MethodsClinical data of Glut1DS patients, including age of onset, clinical manifestations, cerebrospinal fluid (CSF) analysis, and SLC2A1 gene variants, were collected and analyzed.ResultsA total of 93 patients with Glut1DS were included, among whom 65 (70%) were classical phenotypes (including 55 early-onset classical cases and 10 late-onset classical cases), and 28 (30%) were non-classical phenotypes. Significant differences were observed among early-onset classical, late-onset classical, and non-classical groups in terms of age of onset (p < 0.001), episodic psychiatric/behavioral abnormalities (p = 0.012), CSF glucose levels (p < 0.001), and the ratio of CSF glucose to blood glucose (p = 0.003). Genetic variant analysis identified 40 previously reported and 32 novel SLC2A1 variants. These variants were classified into three types: Type A (missense and in-frame indel variants, n = 52), Type B (frameshift, nonsense, splicing site, and initiation codon variants, n = 32), and Type C (single/multiple exon or whole-gene deletions, n = 9). No statistically significant difference was found in the distribution of these three genotypes across early-onset classical, late-onset classical, and non-classical phenotype. However, there were differences in age of onset among the three genetic variant groups (p = 0.009), with Type A variants showing a later age of onset compared to Type B variants (p = 0.014). No significant differences were observed among the three variant groups regarding CSF glucose levels, the ratio of CSF glucose to blood glucose, or CSF lactate levels. Furthermore, patients with identical variants exhibited phenotypic variability, for example, among eight patients (9%) harboring the c.997C>T (p.Arg333Trp) variant, six had early-onset classical phenotypes, while two had non-classical phenotypes.ConclusionGlut1DS predominantly manifests as the classical phenotype, with the early-onset classical phenotype presenting at the youngest age and exhibiting the most severe clinical symptoms. Patients with this type also showed lower CSF glucose levels and a lower CSF glucose to blood glucose ratio compared to other types. Missense and in-frame indel variants were associated with a later age of onset compared to other types of genetic variants. No significant correlations were found between genotype and clinical classification or CSF glucose levels.